Evaluation of Farms’ Sustainability According to Land Tenure in Mornag, Tunisia - Gara, Anissa; Aounallah, Mohamed Karim; Ajabi, Dorra (Universitas Sebelas Maret, 2021)
In Tunisia the main objective of sustainable agriculture is to improve agricultural systems by creating more wealth and meeting the needs of the population without compromising those of future generations. It turned out that confusion and lack of clarity of ownership status of agricultural land would lead to instability in agricultural sustainability by having a negative impact on social and economic prosperity and environment preservation. Within this environmental concern, the current research constitutes an assessment of the level of sustainability of different farms in Tunisia where problems of land ownership still exist. The current research is based on the Farm Sustainability Indicators method (standing for: ‘Indicateurs de durabilité des exploitations agricoles or IDEA). This case study employed IDEA method which provides operational content to compare the sustainability concept at the farm level, based on the factor of ‘land tenure status’. In Tunisia, the lack of clear land ownership affects the output of agriculture that is why it is valuable to assess the impact of land properties status on farms’ agricultural sustainability. Hence, we distinguished two groups of farms: Private Farms (PF) (inherited from father to son) and Farming Enhancement Corporation (FEC) (state’s lands leased by farmers for many years). The results showed that land tenure has impact on farms sustainability. PF are more sustainable on both agro-ecological scale (49.2) and socio-territorial scale (48); compared to FEC (agro-ecological: 44.5 and socio-territorial: 46). PF favor integrated systems and the production of field crops and fodder crops and they attach greater importance to their employees’ training.